Pasal 9 Konstitusi Jepang: Perubahan Sikap AS Terhadap Militer Jepang - Putri, Helsi Eka (Nation State: Journal of International Studies, 2018)
This article explains the US foreign policy on the Obama administration towards the reinterpretation of article 9 of the Japanese constitution. Historically, article 9 was the result of US interference to keep Japan from proactive military activities and oblige Japan to sacrifice all its territory since 1895, and to incorporate Japan into the US security system. This evoke a question, why in the era of Obama administration US supported article 9 reinterpretation efforts that will make the Japanese military proactive? The purpose of this article is to analyze the direction of US President Barack Obama's foreign policy in the second period. Foreign policy theory with national interest concept approach is used to analyze three factors influencing US foreign policy to support the reinterpretation of article 9. This article uses literature study by collecting data that related to the factors of US in doing such foreign policy towards Japan. Ultimately, this article argued that external, internal, and perceptions of US decision-makers influence US foreign policy in favor of reinterpretation of article 9.